2021
DOI: 10.1039/d0qo01466d
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic dimensions to the C–H functionalization of the carbocyclic core in indoles: a review update

Abstract: An integration of two dynamic research paradigms- organocatalysis and remote C-H bond functionalization has together emerged as a profound competition to the conventional transition-metal catalyzed processes. In the contemporary research...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Docking studies revealed that the active compound F7-2 binds to the active pocket of the Bcl-2 protein through a hydrogen bond with Arg143 and the π–π interaction with Ph109 and Phe101. A number of 2,3-dihydrobenzo[f][ 1 , 4 ]oxazepine derivatives were prepared as antagonists of the prostaglandin E2 receptor subtype 2 (EP2) [ 175 ]. The oxazepine derivative with a 4-fluoroindole substituent F7-3 showed a binding affinity of 8 nM for the hEP2 receptor and an IC 50 value of 50 nM in the hEP2 cAMP assay.…”
Section: N -Arylated Indoles As Biologically Active Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Docking studies revealed that the active compound F7-2 binds to the active pocket of the Bcl-2 protein through a hydrogen bond with Arg143 and the π–π interaction with Ph109 and Phe101. A number of 2,3-dihydrobenzo[f][ 1 , 4 ]oxazepine derivatives were prepared as antagonists of the prostaglandin E2 receptor subtype 2 (EP2) [ 175 ]. The oxazepine derivative with a 4-fluoroindole substituent F7-3 showed a binding affinity of 8 nM for the hEP2 receptor and an IC 50 value of 50 nM in the hEP2 cAMP assay.…”
Section: N -Arylated Indoles As Biologically Active Substancesmentioning
confidence: 99%
“…An example of such a compound is sertindole, which is used as an antipsychotic drug [ 3 ]. Due to the significant biological activity of the indole derivatives, much attention has been paid to the modification of the indole unit [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[220] redox catalysis, there are also other potentially metal-free approaches that may be investigated in the context of polymer upcycling. These could include organocatalyzed CÀ H functionalization methods, [221][222][223] aerobic CÀ H functionalization strategies that use molecular O 2 as a sustainable oxidant in place of metal catalysts, [224] metal-free electrochemical oxidative CÀ H trifluoroalkylations, [225][226][227] and biocatalytic methods that employ artificial enzymes for direct and selective CÀ H functionalization. [228,229] This list is not exhaustive and many new methodologies emerging from the field of organic synthesis can conceivably be applied to polymer upcycling, though the efficacy of such reactions on polymers will remain an open question until further investigations can be carried out.…”
Section: Polymer Upcycling Via Organocatalyzed And/or Transition-meta...mentioning
confidence: 99%
“…[220] Angewandte Chemie Aufsätze redox catalysis, there are also other potentially metal-free approaches that may be investigated in the context of polymer upcycling. These could include organocatalyzed CÀ H functionalization methods, [221][222][223] aerobic CÀ H functionalization strategies that use molecular O 2 as a sustainable oxidant in place of metal catalysts, [224] metal-free electrochemical oxidative CÀ H trifluoroalkylations, [225][226][227] and biocatalytic methods that employ artificial enzymes for direct and selective CÀ H functionalization. [228,229] This list is not exhaustive and many new methodologies emerging from the field of organic synthesis can conceivably be applied to polymer upcycling, though the efficacy of such reactions on polymers will remain an open question until further investigations can be carried out.…”
Section: Polymer Upcycling Via Organocatalyzed And/or Transition-meta...mentioning
confidence: 99%